Improving Learning Outcomes of Pancasila Education through the Problem-Based Learning Model - Elin Marlina; Adrias Adrias; Reinita Reinita; Yeni Erita (FKIP - Universitas Riau, 2026)
This study was motivated by the low learning outcomes of fifth-grade elementary school students in Pancasila Education, particularly on the Bhinneka Tunggal Ika element, due to teacher-centered instructional practices that limited students' active participation and critical thinking. The study aimed to improve students' learning outcomes through the implementation of the Problem-Based Learning (PBL) model. This research employed a Classroom Action Research (CAR) design using qualitative and quantitative approaches. The study was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The participants were one teacher and 26 fifth-grade students at SD Negeri Ganting. Data were collected through observation, interviews, tests, and documentation, and analyzed descriptively. The findings revealed that the implementation of the PBL model successfully improved students' learning outcomes and classroom engagement. The average learning score increased from 74 in Cycle I to 89 in Cycle II. Teacher and student activities during the learning process also showed substantial improvement and reached the very good category. These findings indicate that the Problem-Based Learning model effectively enhances students' learning outcomes in Pancasila Education, particularly on the Bhinneka Tunggal Ika element, by promoting active participation, critical thinking, collaboration, and meaningful learning experiences.